KEMENANGAN AKTOR POLITIK GENERASI Z DALAM PEMILIHAN UMUM (PEMILU) LEGISLATIF KABUPATEN WONOSOBO TAHUN 2024 - Dwi Prastyanto; Fitriyah Fitriyah (Journal of Politic and Government Studies, 2025)
The 2024 legislative elections in Wonosobo Regency revealed a growing trend of involvement by young political actors, particularly from Generation Z, who successfully secured seats in the Regional People’s Representative Council (DPRD). This phenomenon is worth examining because local politics has traditionally been dominated by more senior actors, making the emergence of young candidates a new dynamic in regional political contests. This study aims to analyze factors such as social capital, political strategies, and the role of political parties in influencing the victory of Generation Z political actors in the 2024 Wonosobo Regency Legislative Elections. This study employs a qualitative approach with a descriptive design. Data collection was conducted through in-depth interviews with informants involved in the electoral process, followed by qualitative analysis to understand the social and political dynamics underlying the victory of Generation Z candidates. The results indicate that the victory of Generation Z political actors was primarily driven by the role of family-based social capital, the candidates’ political strategies, and political party support within the context of local political culture. Family social capital, consisting of trust, social norms, and social networks —as per Putnam’s indicators— serves as the primary foundation for building political legitimacy within the community. Additionally, political strategies that combine a defensive approach to maintain the support base with an offensive strategy to expand voter support further strengthen the candidate’s electoral mobilization. Thus, the victory of Generation Z candidates in Wonosobo Regency is the result of the integration of the power of family social capital, adaptive political strategies, and party organizational support within the local social structure.